ANALISIS PENDAPATAN USAHA TANI KELAPA DALAM DI DESA SUNGAI BESAR KABUPATEN KUBU RAYA - Kristianto, Evan; S, Bambang Genjik; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe purpose of this research was to find out how the creativity and income of the community in processing deep coconut. This research was conducted in Sungai Besar Village, Batu Ampar District, Kubu Raya Regency. This research uses a qualitative approach with the type of case study. Data collection techniques using interviews, observation, and documentation. The results of interviews and observations with the number of informants 6 people. The results showed that; (1) Coconut processing creativity consists of; copra, crested coconut, shell charcoal, coconut oil and soy sauce. (2) The process in coconut processing consists of; climbing coconuts, collecting coconuts, removing coconuts from the garden, stripping coconut husks, and cutting coconuts. (3) Coconut processing income consists of; sales of copra, crested coconut and shell charcoal, while coconut oil and soy sauce are for personal consumption only. The products of coconut processing are copra, crested coconut and shell charcoal which are produced to be sold to earn income for their own welfare. Coconut oil and soy sauce are not for sale, because other farmers can also produce their own, so coconut oil and soy sauce are for individual consumption only.Keywords: Income, Coconut Farming, Copra